The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/en16207137
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Learning in the Transformer Model for Thermal Comfort Prediction: A Case of Limited Data

Xin Zhang,
Peng Li

Abstract: The HVAC (Heating, Ventilation, and Air Conditioning) system is an important component of a building’s energy consumption, and its primary function is to provide a comfortable thermal environment for occupants. Accurate prediction of occupant thermal comfort is essential for improving building energy utilization as well as health and work efficiency. Therefore, the development of accurate thermal comfort prediction models is of great value. Deep learning based on data-driven techniques has excellent potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The study compares with the existing study ( Zhang & Li, 2023 ) as shown in Table 3 . According to Zhang & Li (2023) , the accuracy is 62.6% accuracy, 57.0% precision, and 59.0% F-score, whereas the proposed method obtained 85.0% accuracy, 86.0% precision, 90.0% recall and 88.0% F-score.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study compares with the existing study ( Zhang & Li, 2023 ) as shown in Table 3 . According to Zhang & Li (2023) , the accuracy is 62.6% accuracy, 57.0% precision, and 59.0% F-score, whereas the proposed method obtained 85.0% accuracy, 86.0% precision, 90.0% recall and 88.0% F-score.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The study compares with the existing study ( Zhang & Li, 2023 ) as shown in Table 3 . According to Zhang & Li (2023) , the accuracy is 62.6% accuracy, 57.0% precision, and 59.0% F-score, whereas the proposed method obtained 85.0% accuracy, 86.0% precision, 90.0% recall and 88.0% F-score. The proposed technique performs better in this context than the Base Paper, indicating that our technique outperforms in thermal comfort model prediction for smart buildings.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The results demonstrated that the ensemble TL approach enhanced the accuracy of thermal comfort predictions for two target subjects using a model pre-trained on a source dataset. In 2023, Zhang and Li [42] proposed integrating transfer learning with a transformer model to predict thermal comfort, utilizing the ASHRAE RP-884 dataset from the Scales project as the source and the Medium US dataset as the target domain. The proposed TL-Transformer model achieved an accuracy of 62.6%, outperforming other state-of-the-art methods tested in their experiments.…”
Section: Thermal Comfort Models With Transfer Learningmentioning
confidence: 99%